De novo protein structure determination by heavy-atom soaking in lipidic cubic phase and SIRAS phasing using serial synchrotron crystallography. (2018) - Botha, S.; Baitan, D.; Jungnickel, K. E. J.; Oberthur, D.; Schmidt, C.; Stern, S.
No abstract available